Hypertonic Saline versus Crystalloids in Patients with Traumatic Brain Injury. (16th November 2020) - Fatima, Nida; Shuaib, Ashfaq
Abstract: INTRODUCTION: Although osmotherapy along with other conventional treatment options, such as sedation, analgesia, head elevation, neuromuscular paralysis, and ventriculostomy, are the rst line treatment in the management of patients with moderate‐to‐severe traumatic brain injury (TBI). METHODS: Electronic databases and grey literature (unpublished articles) were searched under different MeSH terms from 1990 to present. Randomized control trials, case-control studies and prospective cohort studies on decompressive craniectomy in TBI (>18‐year‐old). Clinical outcome measures included Glasgow Coma Outcome Scale (GCOS), Extended GCOS, and mortality. Data were extracted to Review Manager Software. RESULTS: A total of 115 articles that met the inclusion criteria were retrieved and analyzed. Ultimately, ve studies were included in our meta‐analysis, which revealed that patients with TBI who had hypertonic saline had no statistically signi cant likelihood of having a good outcome at discharge or 6 months than those who had crystalloid (odds ratio [OR]: 0.01; 95% con dence interval (CI): 0.03-0.05; P  = .65). The relative risk (RR) of mortality in hypertonic saline versus the crystalloid at discharge or 6‐month is RR: 0.80; 95% CI: 0.64-0.99; P  = .04. The subgroup analysis showed that the group who had hypertonic solution signicantly decreases the number of interventions versus the crystalloid group OR: 0.53; 95% CI: 0.48-0.59; P < 0.00001 and also reduces the length of intensive care unit stay (OR: 0.46; 95% CI: 0.21-1.01; P  = .05). CONCLUSION: Hypertonic saline decreases the nancial burden, but neither impacts the clinical outcome nor reduces the mortality. However, further clinical trials are required to prove if hypertonic saline has any role in improving the clinical and neurological status of patients with TBI versus the normal saline/lactated Ringers.